Egypt at its origins 5 : proceedings of the Fifth International Conference "Origin of the State, Predynastic and Early Dynastic Egypt" Cairo,13th-18 April 2014 - Midant-Reynes, Béatrix.; Tristant, Yann. (Orientalia Lovaniensia analecta, 2017)
This volume presents the results of the latest research and discoveries in the field, which are leading to a better understanding of the origins of the Ancient Egyptian civilization. The 39 articles are organised under five major headings: settlements and domestic activities, mortuary archaeology, technology: pottery and lithic production, iconography and writing, and rock art. They provide new insights into the variety of factors contributing to the rise of the distinct form of the early Egyptian state. Recent discoveries from major sites such as Hierakonpolis, Abydos, and Buto, are the subject of different articles, but also other sites, such as Abu Rawash and the Naqada region, are discussed.